At the Origins of Medical Liability in the West: The Roman Legal Experience Between the First Century BCE and the First Century CE (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
The essay examines the earliest considerations concerning physicians’ liability in ancient Rome, as elaborated by jurists active between the first century BC and the first century CE, a development that significantly coincides with the consolidation of medical practice in Rome. The texts of the classical jurists preserved in the Digest reveal that particular emphasis was placed on cases in which physicians caused harm to slaves, thereby producing an economic loss for their owners, a loss that was actionable and compensable under the Lex Aquilia. Equally noteworthy is the jurists’ treatment of the concept of fault (culpa), which was articulated primarily in terms of lack of professional skill (imperitia). The paper thus contributes to the understanding of the conceptual origins of professional liability in Western legal thought.
Keywords: Roman law; medical liability; Roman jurist; Justinian’s Digest; Lex Aquilia